(3QSGdI ZdWGJ GdYhGes - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYdfG ef ReQI ef Yde hHYO aEf Chdi eG jLH Cf jYde hChdi eG jHPd ajg Gdgee EbGeI GddSGfg hUhfg s
(3BNQgG (B:s
(3dGf GdTF dGjVGa Edi faSg GfJgi hGdYhGe jbhdhf YQb GdfSG HGdcSQ hGdeO hdGjYQa dg EPG GdeYfi ai HWf GdTGYQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSI hGdYTQhfs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GddZIs